Characterization of Detergent Insoluble Proteome in Chronic Traumatic Encephalopathy. Issue 1 (14th November 2017) - Cherry, Jonathan D; Zeineddin, Ahmad; Dammer, Eric B; Webster, James A; Duong, Duc; Seyfried, Nicholas T; Levey, Allan I; Alvarez, Victor E; Huber, Bertrand R; Stein, Thor D; Kiernan, Patrick T; McKee, Ann C; et al.
Abstract: Quantitative proteomics of postmortem human brain can identify dysfunctional proteins that contribute to neurodegenerative disorders like Alzheimer disease (AD) and frontotemporal dementia. Similar studies in chronic traumatic encephalopathy (CTE) are limited, therefore we hypothesized that proteomic sequencing of CTE frontal cortex brain homogenates from varying CTE pathologic stages may provide important new insights into this disorder. Quantitative proteomics of control, CTE and AD brains was performed to characterize differentially expressed proteins, and we identified over 4000 proteins in CTE brains, including significant enrichment of the microtubule associated protein tau. We also found enrichment and pathologic aggregation of RNA processing factors as seen previously in AD, supporting the previously recognized overlap between AD and CTE. In addition to these similarities, we identified CTE-specific enrichment of proteins which increase with increasing severity of CTE pathology. NADPH dehydrogenase quinone 1 (NQO1) was one of the proteins which showed significant enrichment in CTE and also correlated with increasing CTE stage. NQO1 demonstrated neuropathologic correlation with hyperphosphorylated tau in glial cells, mainly astrocytes. These results demonstrate that quantitative proteomic analysis of CTE postmortem human brain can identify disease relevant findings and novel cellular pathways involved in CTE pathogenesis.